Reptile-associated salmonellosis in children aged under 5 years in South West England. Issue 4 (22nd December 2014) - Murphy, Dan; Oshin, Femi
Abstract : Objective: To determine the proportion of Salmonella cases in children aged <5 years that were reptile-associated salmonellosis (RAS) and to compare the severity of illness. Design: To analyse all cases of salmonellosis reported to public health authorities in children aged under 5 years in the South West of the UK from January 2010 to December 2013 for reptile exposure, age, serotype, hospitalisation and invasive disease. Results: 48 of 175 (27%) Salmonella cases had exposure to reptiles. The median age of RAS cases was significantly lower than non-RAS cases (0.5 vs 1.0 year). RAS cases were 2.5 times more likely to be hospitalised (23/48) compared with non-RAS cases (25/127; p=0.0002). This trend continued in cases aged under 12 months, with significantly more RAS cases hospitalised (19/38) than non-RAS cases (8/42; p=0.003). Significantly more RAS cases had invasive disease (8/48: 5 bacteraemia, 2 meningitis, 1 colitis) than non-RAS cases (4/127: 3 bacteraemia, 1 meningitis). Conclusions: Reptile exposure was found in over a quarter of all reported Salmonella cases in children under 5 years of age. RAS is associated with young age, hospitalisation and invasive disease.